2022
DOI: 10.3390/nano12101692
|View full text |Cite|
|
Sign up to set email alerts
|

Fluorinated PEG-PEI Coated Magnetic Nanoparticles for siRNA Delivery and CXCR4 Knockdown

Abstract: CXC chemokine receptor 4 (CXCR4) is a promising therapeutic target. Previous studies have shown that intracellular delivery of siRNA to knockdown CXCR4 expression in cancer cells is an effective therapeutic strategy. To prepare efficient magnetic nucleic acid carriers, it is now necessary to improve the endocytosis efficiency of PEGylated magnetic nanoparticles. In our work, Heptafluorobutyryl-polyethylene glycol-polyethyleneimine (FPP) was first prepared and then used to coat magnetic nanoparticles (MNPs) to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 55 publications
0
10
0
Order By: Relevance
“…Considering the results of electrophoretic mobility and the CpG ODNs’ loading efficiency, ASC NPs were prepared at an AS/CpG ODNs weight ratio of 5:1. Coating and modification with positive potential cationic polymers (such as PEG-bPEI) are common means to convert nanoparticles into siRNA carriers [ 48 , 49 ]. Finally, ASCP NPs were prepared by mixing ASC NPs with PEG-bPEI at the weight ratio of 5:1 and by night stirring and centrifugation.…”
Section: Resultsmentioning
confidence: 99%
“…Considering the results of electrophoretic mobility and the CpG ODNs’ loading efficiency, ASC NPs were prepared at an AS/CpG ODNs weight ratio of 5:1. Coating and modification with positive potential cationic polymers (such as PEG-bPEI) are common means to convert nanoparticles into siRNA carriers [ 48 , 49 ]. Finally, ASCP NPs were prepared by mixing ASC NPs with PEG-bPEI at the weight ratio of 5:1 and by night stirring and centrifugation.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, the SPIOs exhibited good MRI contrast effects. In another study, the surface of the SPIOs is modified with heptafluorobutyryl-PEG-PEI molecules and complexed with siRNA specific to CXCR4 (C-X-C chemokine receptor 4) [131]. Usually, CXCR4 is overexpressed in many cancers (especially breast cancers) as it involves in promoting metastasis, forming new tumor blood vessels and developing resistance to chemotherapeutic drugs.…”
Section: Other Sirnasmentioning
confidence: 99%
“…PEG has been used as a shell in many nano‐drug delivery systems (NDDSs) to reduce toxic effects and overcome the reticuloendothelial system (RES) in the body 17 . Studies have shown that chemical modification of PEI‐coated IONPs with PEG effectively reduced the positive surface charge of nanoparticles and thus improved the stability and safety of nanoparticles in a physiological environment 18,19 . However, reduction of positive charge through PEGylation inhibit the cellular uptake of nanoparticles at the target site 20 .…”
Section: Introductionmentioning
confidence: 99%
“…17 Studies have shown that chemical modification of PEI-coated IONPs with PEG effectively reduced the positive surface charge of nanoparticles and thus improved the stability and safety of nanoparticles in a physiological environment. 18,19 However, reduction of positive charge through PEGylation inhibit the cellular uptake of nanoparticles at the target site. 20 To overcome this PEG dilemma, smart shell-sheddable NPs have been developed that could shed their hydrophilic shells in response to environmental stimuli, such as redox [21][22][23][24] and pH 25 at the extracellular compartment of tumor.…”
mentioning
confidence: 99%